Strength Performance Across the Oral Contraceptive Cycle of Team Sport Athletes: A Cross-Sectional Study - Reif, Astrid; Wessner, Barbara; Haider, Patricia; Tschan, Harald; Triska, Christoph (Frontiers in Physiology, 2021)
Oral contraceptive pills (OCP) are very popular in female athletes not only for contraceptive effects but also due to the possibility of cycle manipulation. Moreover, it is debatable whether manipulation of menstrual cycle has a beneficial effect on exercise performance. Therefore, the aim of this study was to investigate potential differences in strength performance of first division team sport athletes between phases of oral contraceptive cycle. Sixteen female handball players (age: 23.3 ± 3.1 yrs; body mass: 67.0 ± 8.52 kg; body stature: 1.68 ± 0.05 m) using a monophasic OCP participated in strength performance tests, once during OCP consumption (CONS) and once during withdrawal (WITH). Tests were performed on a dynamometer to measure lower body maximal voluntary isokinetic and isometric torque. Prior to each test, body mass was assessed, and venous blood samples were collected. Wilcoxon signed-rank test and magnitude-based inferences have been conducted to analyze differences between WITH and CONS. Significance was accepted at P < 0.05. No significant differences between oral contraceptive cycle phases of strength parameters and body mass have been indicated (all at P > 0.05). Follicle-stimulating hormone (P = 0.001) and luteinizing hormone (P = 0.013) were significantly higher in WITH while estradiol and progesterone, showed no significant difference between phases (both at P > 0.05). These results support the notion that isokinetic and isometric strength performance does not differ between phases of oral contraceptive cycle in well-trained team sport athletes. OCP intake is suggested to cause a stable but downregulated hormone cycle which has no effect on lower body strength performance when comparing oral contraceptive cycle phases. Therefore, manipulation of the female cycle using OCP in order to achieve a higher strength performance does not seem to be justified.